Sintasan dan Pertumbuhan Ikan Nila Merah (Oreochromis sp.) yang Dipelihara pada Sistem Yumina dan Bumina - Muhamad Fauzan Sadina Putra; Sisi Astuti; Khoiri Khabibillah Mahmud; Fina Nabila; Hendri Irawan; Paulina Lorenza; Mirna Fitrani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Putra MFS, Astuti S, Mahmud KK, Nabila F, Irawan H, Lorenza P, Fitrani M. 2021. Survivality and growth of red tilapia (Oreochromis sp.) maintained in yumina and bumina systems. In: Herlinda S et al. (Eds.), Prosiding Seminar NasionalLahan Suboptimalke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 788-794. Palembang: Penerbit&PercetakanUniversitasSriwijaya (UNSRI). Fish farming is a source of livelihood for the community. However, in fish farming, especially tilapia, with high stocking rates, it will result in environmental pollution, both from undigested feed and too much fish manure. One technique that can overcome this is using yumina and bumina. This cultivation technique combines vegetables with fish or fruits with fish. By doing this technique, it will not damage the environment due to the use of fish manure which is used as fertilizer for plants. Yumina-bumina is the right solution because it is environmentally friendly, water quality can also be improved with this technique, because a decrease in water quality will cause fish death. This paper aimed to determine the effect of survival and growth of red tilapia cultured using yumina, bumina, and without yumina and bumina cultivation systems. Based on the results of the journal with 3 treatments, the highest weight growth value of tilapia was in the treatment of tilapia cultivation using pakcoy, and eggplant with results of 27.5 g and 27.2 g, respectively. As for the control treatment, the result was 18.7 g. In addition to pakcoy and eggplant, the yumina and bumina techniques can use basil, kailan, and other plants to get optimal fish growth results. Thus, the growth of tilapia using yumina and bumina techniques resulted in higher growth than without using yumina and bumina, and obtained two advantages in cultivation, namely vegetables and fish or fruit and fish.